Production Efficiency of Seaweed Farming in Tarakan North Borneo - Banyu Riatiga; Dwidjono Hadi Darwanto; Lestari Rahayu Waluyati (Agro Ekonomi, 2017)
This study aims to determine: (1) the factors that inﬂ uence the production of seaweed and (2)  the level of technical efﬁ ciency obtained by seaweed farmers in Tarakan. Since 2009, most of the ﬁ shermen on the coast of Amal turned into seaweed farming as it is more proﬁ table and easier to cultivate. The basic method used in this research is descriptive method while the location of the research was determined by intentional or purposive sampling. The sample selection for seaweed farmer respondents used simple random sampling of 100 seaweed farmers. The results showed that the factors of production which have positive and signiﬁ cant impact on seaweed production in Tarakan are farm area, seeds, labor and dummy for location. The technical efﬁ ciency in a secure or unsecured locations are 0,93 and 0,82, respectively, with the average value of the technical efﬁ ciency of seaweed farmers in general is 0,92. Socio-economic factors affecting technical inefﬁ ciency are farmers’age, farming experience, number of family members, education and dummy for location. However, the experience of farming and dummy for location have negative coefﬁ cients which means that both are able to increase the level of technical efﬁ ciency of seaweed farming.